2022
DOI: 10.1186/s43141-022-00298-4
|View full text |Cite
|
Sign up to set email alerts
|

Stain removing, juice-clarifying, and starch-liquefying potentials of amylase from Pleurotus tuberregium in submerged fermentation system

Abstract: Background Amylase is used commercially in food, textiles, sugar syrup, paper, and detergent industries. Bacteria and fungi remain a significant source of industrial enzymes. Pleurotus tuberregium is a macro-fungi that can exist as a fruiting body, sclerotium, mycelium, and spores. Some studies have been conducted on this fungus, with minimal studies on its enzyme activity (s) using the submerged fermentation technique. Results The purified amylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Another study showed that 7.9-fold purification with a 53.33% enzyme yield from B. cereus GA6 (Roohi et al, 2013). The variations in microbial strains and purification techniques may be responsible for variations in amylase percentage yields (Bamigboye et al, 2022). The molecular weight of the purified enzyme was found to be 55 kDa based on SDS-PAGE as well as zymographic analysis which is concomitant with that of B. cereus GA6, and Bacillus sp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study showed that 7.9-fold purification with a 53.33% enzyme yield from B. cereus GA6 (Roohi et al, 2013). The variations in microbial strains and purification techniques may be responsible for variations in amylase percentage yields (Bamigboye et al, 2022). The molecular weight of the purified enzyme was found to be 55 kDa based on SDS-PAGE as well as zymographic analysis which is concomitant with that of B. cereus GA6, and Bacillus sp.…”
Section: Discussionmentioning
confidence: 98%
“…The pH stability is also an important factor for industrial applications. Amylase that would retain its activity at a specific pH would be a viable candidate for such uses (Bamigboye et al, 2022). The stability of the α-amylase enzyme from S. mobaraensis DB13 at pH 6.0, 7.0 and 8.0 after 90-120 min of incubation at 50°C suggests that the enzyme could be suitable for industrial application.…”
Section: Discussionmentioning
confidence: 99%
“…Liquefaction enzymes (deactivation temperature about 100 °C) were not completely inactivated when the temperature increased, but the glucoamylase (the optimum temperature is 35 °C) that decomposed polysaccharides into oligosaccharides and monosaccharides was easily inactivated at high temperatures International Journal of Food Science and Technology 2023 (Fig. 3b; Bamigboye et al, 2022). This showed that when the temperature of the fermentation system was close to the maximum temperature, the accumulated polysaccharides in the fermentation system were difficult to decompose; yet, the microbial metabolism continued, and instead, the small molecular sugars accumulated in the system were consumed, reducing their content.…”
Section: Analysis Of Polysaccharides and Oligosaccharides Metabolism ...mentioning
confidence: 99%
“…LWT-Food Science and Technology, 130, 109620. Li, W., Fan, G., Fu, Z. et al (2020) Bacillus licheniformis affects the microbial community and metabolic profile in the spontaneous fermentation of Daqu starter for Chinese liquor making. International Journal of Food Microbiology, 250, 59-67.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation